Non-performing loans and their impact on the credit capacity of com (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract:                The banking system is primarily a credit system, and the lending function is considered the basis of banking work and the most profitable activity, and at the same time banksThe bankerIt suffers fromz significant risks that hinder the proper process of credit activities and limit its required effectiveness .Increasing the granting of credit necessarily contributes to raising rates of economic development.and this isThe impact depends greatly on the extent of allocation and distribution of bank credit to the most productive uses in the economy and profitable projects, because granting bank credit to unprofitable projects will increase the default in loan repayments according to the agreed upon schedule and then reduce the granting of credit in the future, which will hinder the pace of economic progress.Hence, the research problem centered on  the following question: -        Does the increase in rates and percentages of non-performing loans in the banking system create the bank’s exposure to the risks of reducing profits and competitive credit capacity??To achieve the research goalIt was completedLearn about the foundations of granting credit and its conditions to reduce non-performing loans AndmeasurementIndicatorsImpact of non-performing loans thenAnalysis of the impact of non-performing loans on bank creditThe study adopted the periodbetweengeneral2020- 2022A sample of government and private banks, and the study reached the following conclusions: That highMeasurement index ratioTotal cash credit to total deposits It is obtained because of the credit granted to private banks through the initiative launched by the Central Bank, and this credit granted is far from the standard of deposits it has..There is an increase in the ratio of non-performing loans to the total cash credit with private banks for the year 2020.The volume of bad debts held by private banks requires them to adhere to proper controls in the process of granting credit through studying the customer’s case, the economic feasibility of the project, etc.Keywords: non-performing loans,And competitive credit capacity,TotalBank credit,Total deposits .